2019
DOI: 10.3892/mmr.2019.9805
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑758 inhibits tumorous behavior in tongue squamous cell carcinoma by directly targeting metadherin

Abstract: Numerous microRNAs (miRNAs) are dysregulated in tongue squamous cell carcinoma (TSCC), and their dysregulation has been demonstrated to have a strong correlation with TSCC progression via regulation of their targets. Therefore, miRNAs have potential use in the diagnosis and treatment of patients with TSCC. In the present study, miRNA-758 (miR-758) expression in TSCC tissues and cell lines was detected through reverse transcription-quantitative polymerase chain reaction, and the effects of miR-758 on TSCC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Three human TScc cell lines, Scc-9, cAL-27 and Scc-15, as well as normal gingival epithelial cells (ATcc ® PCS-200-014™) were purchased from the American Type Culture Collection (ATCC). Previous studies (26,27) have used the normal gingival epithelial cells as a control for TScc cell lines. dulbecco's modified Eagle's medium (dMEM) supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin solution (all Invitrogen; Thermo Fisher Scientific, Inc.) was utilized for cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…Three human TScc cell lines, Scc-9, cAL-27 and Scc-15, as well as normal gingival epithelial cells (ATcc ® PCS-200-014™) were purchased from the American Type Culture Collection (ATCC). Previous studies (26,27) have used the normal gingival epithelial cells as a control for TScc cell lines. dulbecco's modified Eagle's medium (dMEM) supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin solution (all Invitrogen; Thermo Fisher Scientific, Inc.) was utilized for cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…Feng CZ’s research [ 45 ] suggested the roles of miRNA-124 in the microglial response to oxidative stress. In vitro, functional experiments revealed that up-regulation of miR-758 inhibited cell proliferation, migration, and invasion [ 46 , 47 ]. Mi-RNAs suppressed the proliferation, manifested as down-regulation in ovarian cancer tissues and cell lines [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-758-3p also inhibits the malignant progression of retinoblastoma by directly targeting PAX6( 37 ). In addition, miR-758-3p also inhibits lung cancer cells ( 38 , 39 ). Based on these findings, it was speculated that miR-758-3p is closely associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%